2007
DOI: 10.1016/j.bbaexp.2007.07.003
|View full text |Cite
|
Sign up to set email alerts
|

YB-1 binds to the MMP-13 promoter sequence and represses MMP-13 transactivation via the AP-1 site

Abstract: Matrix metalloproteinases (MMPs) are key enzymes that implement degradation of the extracellular matrix during cellular invasion in development, tissue remodeling, and pathogenic disease states. MMP-13 has pivotal roles in the pathogenesis of invasive cancers and arthritis. Here we report the identification of Y-box binding protein-1 (YB-1) as a new repressor of MMP-13 transactivation. YB-1 binds in vitro in DNA affinity chromatography to the activator protein-1 (AP-1) DNA sequence within the MMP-13 promoter. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 45 publications
0
24
0
Order By: Relevance
“…The transcription factor Runt domain factor-2 (Runx-2) binds at a unique site on the MMP-13 promoter, and also interacts with AP-1 to mediate MMP-13 transcription (49,50). Recently, YB-1, a member of the Y-box family of DNA-binding proteins, was shown to directly bind at the AP-1 site on MMP-13 and regulate its transcription (51). Thus, the AP-1 binding site on the promoter region of the MMP-13 gene plays a critical role in MMP-13 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…The transcription factor Runt domain factor-2 (Runx-2) binds at a unique site on the MMP-13 promoter, and also interacts with AP-1 to mediate MMP-13 transcription (49,50). Recently, YB-1, a member of the Y-box family of DNA-binding proteins, was shown to directly bind at the AP-1 site on MMP-13 and regulate its transcription (51). Thus, the AP-1 binding site on the promoter region of the MMP-13 gene plays a critical role in MMP-13 gene expression.…”
Section: Discussionmentioning
confidence: 99%
“…Raffetseder et al (2009) reported that YB1 could upregulate chemokine ligand 5 (CCL5) transcription in monocytes, while repressing CCL5 transcription in differentiated macrophages. YB1 repression of matrix metalloproteinase-13 (MMP-13) expression through binding of the adaptor protein-1 (AP-1) site of the MMP-13 promoter has also been demonstrated, and MMP-13 repression by YB1 can play a pivotal role in the pathogenesis of invasive cancers and arthritis (Samuel et al, 2007). Furthermore, Evdokimova et al (2009) demonstrated that YB1 protein level elevation is associated with reduced proliferation rates in disseminated mesenchymal-like breast carcinoma cells.…”
Section: Introductionmentioning
confidence: 96%
“…YB1 can recognize and bind specific promoter sequences containing the 5¢-CTGATTGG-3¢ motif (the so-called Y-box motif) through its CSD domain and can both positively and negatively regulate the expression of a large number of genes involved in proliferation and differentiation (Kosnopfel et al, 2014). YB1 was subsequently found to bind other DNA sequences, such as AP-1 binding sites (Samuel et al, 2007) and single-stranded DNA (ss-DNA) sequences (C/T-or GC/GA-rich sequences) (Izumi et al, 2001;Zasedateleva et al, 2002). Two of our recent studies have demonstrated YB1 interaction through its C-terminal domain (CTD) with a GGGCGG motif (known as a GC-box) in the promoters of proliferation and differentiation-related genes in vascular smooth muscle cells (VSMCs).…”
Section: Introductionmentioning
confidence: 99%
“…ANKRD1 interaction with the nuclear factor YB-1 at a hypoxia-inducible factor 1 site in the myosin light-chain 2v (MLC 2v) promoter negatively regulates myosin expression (10). YB-1 has also been shown to interact with the AP-1 site within the MMP-13 promoter, and its overexpression potently represses AP-1-dependent transactivation (49). Interestingly, nucleolin and YB-1 interact with each other, and both proteins bind to RNA to form a complex (50).…”
Section: Figmentioning
confidence: 99%